The development of a prototype kiosk program and its potential for use in the UP Law Library - Romero, Robert Matthew C. (Institute of Library Science, University of the Philippines Diliman, 2002)
The study aimed at developing a prototype-kiosk program and determining its potential for use in the UP Law Library. The study also aimed at determining which features of the prototype-kiosk program were useful to the respondents. Finally, it looked into the general attitude of the users towards the existence of such devices inside libraries. The development of the program underwent several stages namely: planning, requirements analysis, architecture design, storyboarding, content production, authoring and evaluation. In determining user reaction towards the program, a structured questionnaire was sampled, revised, and distributed to 75 library users.